2010
DOI: 10.1016/j.neulet.2010.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 upregulates the expression of PMP22 in cultured rat Schwann cells via a JAK2-dependent pathway

Abstract: The interleukin-6 (IL-6) family of cytokines is thought to be involved in the development and regeneration of peripheral nerves; however, their roles in myelination remain unclear. In this study, we examined the effects of IL-6 on the expression of genes for compact myelin proteins using Schwann cell cultures prepared by multiple explantation of adult rat sciatic nerves. In semi-quantitative reverse transcription-polymerase chain reaction analysis, stimulation of Schwann cells with IL-6 significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Both Schwann cells and astrocytes are known to have receptors for these cytokines (Klein et al, 1997; Lee et al, 2009a, b; Wang et al, 2009; Ito et al, 2010; Kirsch et al, 2010), as do macrophages (Hendriks et al, 2008). An interesting example of a quite complicated set of intercellular processes involving LIF concerns this cytokine's ability to stimulate myelination (Ishibashi et al, 2006).…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Both Schwann cells and astrocytes are known to have receptors for these cytokines (Klein et al, 1997; Lee et al, 2009a, b; Wang et al, 2009; Ito et al, 2010; Kirsch et al, 2010), as do macrophages (Hendriks et al, 2008). An interesting example of a quite complicated set of intercellular processes involving LIF concerns this cytokine's ability to stimulate myelination (Ishibashi et al, 2006).…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Exogenous administration of low-dose IL-6 to treat DPN  may be beneficial due to (1) increased insulin sensitivity in muscle (49), (2) decreased systemic inflammation (43, 44), (3) increased remyelination of axons (8183), (4) increased nerve regeneration (9698), (5) increased lipolysis (47, 48), and (6) decreased insulin secretion (34, 47). …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, given studies in STZ-induced diabetic models have shown that delayed Wallerian degeneration is related to impaired axonal regeneration (79, 80), it may be inferred that in the diabetic state a lack of sufficient IL-6 signaling in Schwann cells may serve to delay Wallerian degeneration, thus further impairing nerve regeneration. In cultured rat Schwann cells, IL-6 upregulates genes for abundant low molecular weight glycoproteins in myelin such as myelin basic protein (MBP), peripheral myelin protein P 0 (81, 82) or peripheral myelin protein 22 (pmp22) via a JAK2-dependent pathway (83). Administration of IL-6/IL-6R fusion protein following nerve transection increased myelinated nerve fiber regrowth by fourfold (82).…”
Section: Il-6 and Schwann Cells: Stimulating Remyelinationmentioning
confidence: 99%
“…PMP22, peripheral myelin protein 22, mediates Schwann cell growth and peripheral myelin compaction. Interleu-kin-6 upregulates the expression of PMP22 in cultured rat Schwann cells via a JAK2-dependent pathway (Ito et al, 2010). PMP22 is up-regulated in leukemia cells after combination treatment with 5-azacytidine and scriptaid.…”
Section: Discussionmentioning
confidence: 95%